How to define the system in social life cycle assessments? A critical review of the state of the art and identification of needed developments - Dubois-Iorgulescu, Ana-Maria; Saraiva, Anna Karin Elisabeth Bernstad; Valle, Rogerio; Rodrigues, Leonardo Mangia (The international journal of life cycle assessment, 2018)
Purpose This literature review aims at fostering the use of social life cycle assessment (SLCA) and improving the robustness of the method by focusing on one primordial element: system boundaries definition. Our goal is to provide an overview of methods used to create the product system and the cut-off criteria applied. Methods We analyse SLCA case studies from peer-reviewed journals and some academic reports published from 2009 until 2015. Amongst the 33 SLCAs identified, 9 are within an life cycle sustainability assessment. We analyse how authors conceptually define the product system and the implications of their different approaches. We also classify and describe the criteria used for cut-off and their justification. Results and discussion We find that two conceptual views of the system exist, and often coexist, in reviewed case studies; one technical approach, defining life cycle stages in terms of technical processes related by material or energy flows, and one description of the system in socio-economic terms, selecting organisations as system units. Those organisations are where technical processes take place or are the economic actors whose functioning is influenced through market and economic ties by the life cycle of the product (consequentially indirect sources of social impacts). Cut-off criteria are applied in 15 cases. They are mostly qualitative, have a high variability in their justifications and are distributed in four groups: social significance, empirical motivations, identical elements and significant dependency and decision relevancy. Two articles conduct a sensitivity analysis, showing radically different results depending on the conceptual view leading the design of the system. Finally, we see that the conceptual view of the system and applied cut-off criteria depend on the objectives of the assessment, the targeted audience and the methodology chosen to conduct the SLCA. Conclusions Differing conceptual approaches of the system and very diverse cut-off criteria used are identified in SLCA case studies. This variability allows a better adaptation of studied systems to the objectives of the assessments. Justifications for system boundaries setting is many times lacking or not systematised. A more rigorous documentation of system boundaries setting in future case studies and research is recommended.